A high efficiency dual‐band outphasing power amplifier design. Issue 2 (12th December 2020) - Wang, Weiwei; Chen, Shichang; Cai, Jialin; Zhou, Xinyu; Chan, Wing Shing; Wang, Gaofeng
Abstract: This article proposes a novel design methodology for dual‐band outphasing power amplifiers (PAs) with back‐off efficiency enhancement. While satisfying load modulation requirements of the Chireix outphasing PA, this work replaces the quarter‐wavelength impedance inverter in the classical structure with a dual‐band impedance inverter. In addition, two dual‐band reactance compensation networks that absorb the transistor parasitic capacitance are strategically placed. This mitigates the intrinsic reactive loading problem of the outphasing PA and also reduces circuit complexity. A comprehensive theoretical formulation of the proposed design is described and verified through the implementation of a dual‐band (2.6 and 3.5 GHz) PA prototype intended for LTE and 5G applications. This amplifier is built upon two 10‐W GaN HEMTs, and achieves a maximum power of 44.6 and 43.5 dBm with over 71% and 64% associated drain efficiencies at 2.6 and 3.5 GHz, respectively. At the 6 dB output back‐off points, corresponding efficiencies reached 58.4% and 50.1%, respectively. According to the best of authors' knowledge, this is the first dual‐band outphasing PA work with comparable performances to other load modulation type PA such as the Doherty.